Reconstruction of Iddah Career Women from the Perspective of Compilation of Islamic Law and Kyai Husain Muhammad - Ismail Marzuki; Qudsiyatut Diana (LPPM Institut Nasional Laa Roiba Bogor, 2023)
In the view of Islam, it does not prohibit women who want to play a role in the public space. In KHI, the iddah has been regulated, whereas in modern times it has become a problem for career women who must continue to be active even during the iddah period because these women have to provide for their family. From this this research will discuss the existing construction so that it can be relevant for women who are will run it especially for career women. And questions began to arise as to why the iddah provision greatly discriminated against women, especially career women and how this construction was discussed by KHI and what kind of feminist scholar KH Husain Muhammad was in interpreting women's role in the public world, and this is a type of normative legal research examining written law from historical aspects. which we will use in this journal, and this research. If we look at the data source used in this type of library research, the results obtained by the author are that some scholars are of the opinion that career women may leave the house, if in an emergency and what is meant by this emergency, ulama' ushul fiqh such as Wahbah al-Zuhaili which interprets the meaning of emergency as an urgent need that must be taken care of. a woman whose husband has died, then she has to feed her family, then she is allowed to leave the house, because she is in an emergency. Keywords: Reconstruction; Iddah; Career woman; Islamic Law Compilation; Kiyai Husain Muhammad.